The Satisfaction Level of Visitors to the Blessing Jesus Statue as a Recreational Object in Buntu Burake Village, Makale District - Murtono, Tri; Suhendra, Tesa Alex; Sardiman, Sardiman; Rifandy, Arief Aditya; Liloi, Delvi Kristanti; Rahmah, Rahmah; Sukrawan, Nyoman; Kungku, Christian (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. The Blessing Jesus Statue Tour stands out as a notable attraction frequently explored by both domestic and international visitors. This investigation seeks to assess the degree of visitor satisfaction regarding the Blessing Jesus Statue as a recreational attraction. Materials and Methods. This investigation employs a descriptive methodology utilizing a survey approach alongside quantitative data analysis. The participants in the investigation consisted of individuals visiting the Blessing Jesus Statue located in Tana Toraja Regency. The participants in this investigation consisted of visitors to the tourist destination, with a sample size of 80 individuals. The sampling method employed was accidental sampling. The analysis of data involved the application of descriptive statistics, utilizing percentage analysis to classify the degree of visitor satisfaction. Results. The findings of the study indicated that one individual (1.25%) fell into the very dissatisfied category, 23 individuals (28.75%) were dissatisfied, 39 individuals (48.75%) reported being quite satisfied, 12 individuals (15%) were satisfied, and 6 individuals (6.25%) expressed being very satisfied. Thus, the majority of visitors rated their level of satisfaction in the quite satisfied category with a percentage of 48.75 % . Conclusions. The findings suggest that visitor satisfaction with the Blessing Jesus Statue tour falls within the fairly satisfied range. To enhance visitor satisfaction, it is recommended that managers focus on upgrading current facilities and services. Additional investigation may explore various elements, including service quality, cleanliness standards, and environmental sustainability, to enhance the appeal of this tourist destination.